Infantile Neuroglycopenia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2007)
Participant 1, a 23-year-old woman with congenital hypoglycemia (hyperinsulinism); participant 2, a 16-year-old boy with genetic mutation of the cerebral glucose transporter type 1 (GLUT1 deficient); and participant 3, the 23-year-old healthy twin sister of participant 1 as a control, received a neurologic examination, PET scan, and neuropsychological evaluation, in a study at Neurological Institute, New York, NY.